PENETAPAN KADAR KLORIN PADA TEPUNG TERIGU YANG BEREDAR DI PASAR BEKASI MENGGUNAKAN METODE SPEKTROFOTOMETER UV-VIS - Fitriani; Shiva Deviana (Postgraduate, University of Mataram, 2026)
Wheat flour is a widely consumed food ingredient produced from the processing of wheat (Triticum spp.) and commonly used as a raw material for various food products. In some processing practices, chlorine may be used as a bleaching agent to produce a whiter flour appearance. However, excessive chlorine levels in food may pose potential health risks. This study aimed to determine the presence and concentration of chlorine levels in wheat flour circulating in traditional markets in Bekasi and to evaluate whether the detected levels comply with the maximum residue limit established in BPOM Regulation No. 28 of 2019 concerning processing aids in food processing, which sets the maximum chlorine residue at 1 mg/kg. A total of nine wheat flour samples were analyzed using qualitative and quantitative methods. The samples were first extracted using chlorine-free water, followed by qualitative analysis based on color changes and quantitative determination using a UV–Vis spectrophotometer with N,N Diethyl-p-phenylenediamine (DPD) reagent. The qualitative results showed that seven out of nine samples were positive for chlorine levels. Quantitative analysis indicated that seven samples exceeded the permitted limit, with the highest level of 9.44 mg/kg found in sample A2. These findings highlight the importance of monitoring chlorine levels in wheat flour to ensure food safety and consumer protection.